Prevalence of Freshly Generated Particles During Pollution Episodes in Santiago de Chile - Rubio-Campos, M; Gramsch-Labra, E (AAGR Aerosol and Air Quality Research, 2016)
A winter campaign was carried out in Santiago de Chile the year 2012 in two urban sites that can be considered representative for most of the city in order to characterize formation of primary and secondary PM1.0 during episodes. One site is located in the campus of the University of Santiago and measurements were carried out with an Aerosol Chemical Speciation Monitor and a black carbon monitor. Another site is located in a large park, about 2 km south-east of the first site, measurements of CO, NOx, SO2, O3 were done in this site. A noticeable increase in most of the primary components of PM1.0 (black carbon and organics) and primary gases (CO and NO) was observed during days in which the average PM1.0 concentration was higher than 50 µg m-3 (episode). A small increase or no change was observed in the secondary pollutants (NH4, NO3, SO4 and NO2) at night during these episodes. Positive Matrix Factorization was used to extract four components from the ACSM data: hydrocarbon-like organic aerosol (HOA), biomass burning OA (BBOA), low volatility oxygenated OA (LV-OOA) and semi-volatile oxygenated OA (SV-OOA). The freshly generated components (HOA and BBOA) showed a clear increase at night during episodes, while the aged fraction of organic aerosol (LV-OOA and SV-OOA) showed a smaller increase or a decrease at night during episodes. Correlation of HOA and BBOA components with primary pollutants was also high, indicating that freshly created aerosols (HOA, BBOA and BC) are in large part responsible for the increase in pollution at night during episodes in Santiago de Chile. © Taiwan Association for Aerosol Research.
Keywords: Pollution episode; Primary particle; Secondary organic aerosol (SOA)